2013
DOI: 10.1007/bf03379594
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Implications on Visual (Color) Representation and Cytochrome Oxidase Blobs

Abstract: The rich concentration of mitochond rial cytochrome oxid ase (CO) blobs in the V1 (striate) primate visual cortex has never been explained . Although the d istribution of CO blobs provid ed a persuasive example of columnar structure in the V1, there are contrad ictions about the existence of hypercolumns. Since photoreceptors and other retinal cells process and convey basically external visible photonic signals, it suggests that one of the most important tasks of early visual areas is to represent these extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…We speculate that blob impairment is a key component of this mechanism. In V1, the P-blob stream is characterized by a higher mitochondrial CO concentration, whereas the P-interblob stream has a lower concentration of CO. CO is well-known to be the last enzyme in the respiratory chain of mitochondria that is related to oxidative metabolism and energy production (Liu and Wong-Riley, 1995 ; Bókkon and Vimal, 2010 , 2013 ) and is closely coupled to neuronal functional activity (Liu and Wong-Riley, 1995 ). It is interesting to note that recent neuroimaging and postmortem studies have reported mitochondrial dysfunction in the brains of ASD individuals (Rossignol and Frye, 2012 , 2014 ).…”
Section: Altered Connectome Functions In Asdmentioning
confidence: 99%
“…We speculate that blob impairment is a key component of this mechanism. In V1, the P-blob stream is characterized by a higher mitochondrial CO concentration, whereas the P-interblob stream has a lower concentration of CO. CO is well-known to be the last enzyme in the respiratory chain of mitochondria that is related to oxidative metabolism and energy production (Liu and Wong-Riley, 1995 ; Bókkon and Vimal, 2010 , 2013 ) and is closely coupled to neuronal functional activity (Liu and Wong-Riley, 1995 ). It is interesting to note that recent neuroimaging and postmortem studies have reported mitochondrial dysfunction in the brains of ASD individuals (Rossignol and Frye, 2012 , 2014 ).…”
Section: Altered Connectome Functions In Asdmentioning
confidence: 99%
“…These re-emitted photons on receptoral stimulation arise from within mitochondrial CO-rich blobs in supragranular layers of V1 and stripes throughout the entire V2. The COrich blobs are the functional unit for phosphene induction and also could be elicited in V3, v4, V5/ MT+, intraparietal sulcus regions [60]. This suggests that, the visual cortex provides widespread units of microenvironment that protects from brain environmental 'decoherence'.…”
Section: Discussionmentioning
confidence: 96%
“…The photoreceptors and other retinal cells would convey photonic signals due to effects of exogenous visible electromagnetic photons. However, photon signals can also arise from within the neural processing apparatus, for example, direct electrical stimulation to neurons of the visual system would cause subjective perception of point of light called phosphenes [60]. The latter suggests that, re-emitted photons could arise at the neural stage in the primary and secondary visual cortex during visual perception.…”
Section: Discussionmentioning
confidence: 99%
“…In V1, the color pathway (blob region) is characterized by a rich concentration of mitochondrial cytochrome oxidase (CO), whereas the form pathway (interblob region) has lower CO concentration. CO is the last enzyme in the mitochondrial respiratory chain engaged in oxidative metabolism and energy production [ 48 50 ], and is closely coupled to neuronal functional activity [ 48 ]. Interestingly, mitochondrial dysfunction in the brains of ASD individuals has been recently reported in neuroimaging and postmortem studies [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%